Trace Level Arsenic Quantification through Cloud Point Extraction: Application to Biological and Environmental Samples - Kempahanumakkagari Suresh Kumar; Malingappa Pandurangappa (The Scientific World Journal)
A sensitive solvent-free extraction protocol for the quantification of arsenic at trace level has been described. It is based on the reaction of arsenic (V) with molybdate in acidic medium in presence of antimony (III) and ascorbic acid as a reducing agent to form a blue-colored arsenomolybdenum blue complex. The complex has been extracted into surfactant phase using Triton X-114, and its absorbance was measured at 690 nm. The detection limit, working range, and the relative standard deviation were found to be 1 ng mL−1, 10–200 ng mL−1, and 1.2%, respectively. The effect of common ions was studied, and the method has been applied to determine trace levels of As(III) and As(V) from a variety of samples like environmental, biological, and commercially procured chemicals.